Effect of reduced and polymerized vegetable oils on the permeability of sand - Tinga, Angelo Patrick F.; Torio-Kaimo, Lestelle V.; Zarco, Mark Albert H. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
The study on the effects of multiple contaminants on soil is now gaining popularity among researchers around the world. As an attempt to further expand the variety of materials studied, this research uses both lauric oil, which is obtained from waste oils from households, and flaxseed oil. The study uses lauric oil in its unused and used form and flaxseed oil in its unused form. For some samples, before the vegetable oil is added to sand, the oil is heat-treated in order to reduce or polymerize the oil such that the results are substances that have greater viscosity. Investigations were done on the soil sample to determine its physical properties such as grain size distribution, specific gravity, and permeability. Varying oil-soil concentrations were prepared to also determine the changes dependent on concentration. The results of the study indicated that as the percentage of lauric oil products increased, the permeability of the sand would decrease. The permeability change of used and unused lauric oils were quite similar and were not statistically significant at a 95% confidence interval. The effect of reduced lauric oil provided a faster decrease in sample permeability versus used lauric oil and was statistically significant at a 90% confidence interval. The polymerized flaxseed sample failed to provide a decrease in permeability, possibly due to the uncontrolled formation of the polymer.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Soil permeability; Soil pollution; Linseed oil; Lauric acid